Implementation of transformative da'wah its implications on character education in marginal children - Jami, Deni Zam; Susanti, Illa (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2023)
Purpose – This study aims to prove that the transformational da'wah carried out by the Bina Insan Kamil Islamic Boarding School Jakarta for marginalized children can impact character education.Method – The method used in this research is a phenomenological method with a qualitative approach. From the phenomenological research, a description of the existing social phenomena is carried out. The primary data source in this study was the result of interviews with the da'wah activists of the Bina Insan Kamil Islamic Boarding School, parents, and marginalized children assisted by the da'wah of the Bina Insan Kamil Islamic Boarding School.Result - The study results show that the transformative da'wah carried out by the Bina Insan Kamil Islamic Boarding School is persuasive, honest work and empowerment adapted to the situation and conditions of marginalized children.Implication – The transformative da'wah carried out by the Bina Insan Kamil Islamic Boarding School has an impact on changing the character of marginalized children. The form of character change is that marginal children look cheerful, enthusiastic, independent, confident, optimistic, and have high fighting power. Empowerment of marginalized children impacts their enthusiasm to study, some return to school, enter Islamic boarding schools, and some are already working. Circles will realize transformative da'wah.Originality – This research is the first study to link the da'wah movement with implications for character changes in marginalized children.***Tujuan - Penelitian ini bertujuan untuk membuktikan bahwa da’wah transformasional yang dilakukan oleh Pondok Pesantren Bina Insan Kamil Jakarta terhadap anak-anak marjinal dapat memberikan dampak terhadap pendidikan karakter.Metode - Metode yang digunakan dalam penelitian ini adalah metode fenomenologi dengan pendekatan kualitatif. Dari penelitian fenomenologi tersebut, dilakukan pendeskripsian terhadap fenomena sosial yang ada. Sumber data primer dalam penelitian ini adalah hasil wawancara dengan para aktivis da’wah Pondok Pesantren Bina Insan Kamil, orang tua, dan anak-anak marjinal dampingan da’wah Pondok Pesantren Bina Insan Kamil.Hasil - Hasil penelitian menunjukkan bahwa da’wah transformatif yang dilakukan oleh Pondok Pesantren Bina Insan Kamil bersifat persuasif, kerja nyata dan pemberdayaan yang disesuaikan dengan situasi dan kondisi anak marjinal.Implikasi - Da’wah transformatif yang dilakukan oleh Pondok Pesantren Bina Insan Kamil berdampak pada perubahan karakter anak marjinal. Bentuk perubahan karakter tersebut adalah anak-anak marjinal terlihat ceria, bersemangat, mandiri, percaya diri, optimis, dan memiliki daya juang yang tinggi. Pemberdayaan anak-anak marjinal berdampak pada semangat belajar mereka, ada yang kembali bersekolah, masuk pesantren, dan ada juga yang sudah bekerja. Lingkaran akan mewujudkan da’wah yang transformatif.Orisinalitas - Penelitian ini merupakan penelitian pertama yang mengaitkan gerakan da’wah dengan implikasi perubahan karakter pada anak-anak yang terpinggirkan.